PERSPEKTIF EKONOMI ISLAM DALAM PERMINTAAN UANG PERNIKAHAN DI DESA LEKOSULA MALUKU UTARA - Asmi Ningsi Umasugi; Arizal Hamizar; Muammar W. Maruapey (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to describe the Islamic Economic view regarding the demand for wedding money in Lekosula Village and the use of wedding money in related businesses in Lekosula Village. This research was carried out using qualitative methods with a field research approach. Inductive analysis techniques are used to explain specific things and then draw conclusions. The results of the research found that the Islamic Economic View in looking at the demand for wedding money given by the prospective groom to the prospective bride, with a fairly high amount, had a negative impact on both the prospective groom and the prospective bride, where the demand for wedding money was such a high number is never taught in Islamic Sharia. Therefore, Islamic Sharia prohibits anything excessive, Islam only requires a dowry and not wedding money, but wedding money is not prohibited if it does not burden the prospective bridegroom. Other findings show that wedding money has a positive impact on entrepreneurs involved in the wedding event and making significant profits.